PENINGKATAN KINERJA PRODUK MELALUI PEMBERDAYAAN DAYA INOVASI (Studi Kasus Pada UKM Batik Tulis Ekspor Surakarta) - Utami Tri Sulistiyorini (Admisi dan Bisnis, 2014)
This research is based on the questions that can not be answered in the first research, those are : (1) How the SME’s Surakarta batik export empower process innovativeness to increase product’s performance; (2) How the SME’s Surakarta batik export empower behavior innovativeness to increase product’s performance; and (3) How the SME’s Surakarta batik export empower behavior innovativeness to increase product’s performance. To answer these questions, this research used qualitative research design with case study approach. This approach is chosen because, this research is aimed to answer the question, how innovativeness is empowered by SME”s Surakarta batik export to increase the product performance.The result of this research show as follow : Behavior innovativeness is empowered by SME’s Surakarta batik export through, benevolence based trust and competence based trust. These trust is really effective to increase the product’s performance.Product innovativeness is empowered effectively by SME’s Surakarta batik export, through the development of ; the leader’s trust toward the supordinates’expertise; the leader’s trust toward the subordinate’s vision forward; and the leader’s trust toward the subordinates’ technology competencies.Process innovativeness is empowered effectively by SME’s Surakarta batik export , through the development of ; the leader’s trust toward the subordinates’ technology competencies; the leader’s trust toward the subordinates’ capabilities to learn and develop continuesly; the leader’s trust toward the subordinate’s kindness; the leader’s trust toward the subordinates’s fulfillment of their promes; the leader’s trust toward the supordinates’expertise; the leader’s trust toward  ; and the leader’s trust toward the subordinate’s vision forward.